Public Funds as a Source of Financing Revalorization of Sacral Historical Monuments: The Example of Poland - Kotlińska, Janina Beata (Religions, 2024)
Sacral historical monuments are primarily places of prayer, but also objects performing numerous other functions. These are public goods, including cultural goods that build national identity. Their preservation in the right condition is important not only for the owner, but also for the public authorities, whose duty is to preserve them for future generations. The study concerns the financing of sacral monuments in Poland. Its aim is to indicate the legitimacy of financing the revalorization of sacral monuments from public funds, the solutions applied in this area in Poland, and the sources and amount of support provided to the owners of these objects in the years 2017–2022. In it, the authors: (1) refer to such concepts as: public good, cultural good and cultural heritage, (2) define—based on Polish regulations—the concept of a sacral monument and indicate the multiplicity of functions that these objects perform, (3) present the number and types of sacral monuments in Poland, taking into account their location, (4) identify available sources of public funds for the revalorization of sacral monuments in Poland. The analyses carried out show that in Poland, every year, public funds play an important role in the revalorization of sacral historical monuments. In real terms, its volume remained at a similar level over the period considered. The methods used in the development are as follows: critical analysis of the literature and legal acts and selected methods of descriptive statistics.